2006
DOI: 10.1300/j295v02n01_03
|View full text |Cite
|
Sign up to set email alerts
|

Citation Help in Databases

Abstract: A review of the help files in several major databases revealed that database vendors have begun including information on citing sources, which has the potential to be very useful to students. Surprisingly, 94% of the citation examples in the databases reviewed had errors. The average number of errors per example was 4.3. The citation help appears to have been put together quickly, with little thought and no proofreading. Librarians must insist that vendors correct or remove this information. [Article copies av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
1
7
1
Order By: Relevance
“…In 2006 when the authors examined the citation help available in databases, the quality of the help was disappointing. The previous study found that 94% of the citation examples examined had errors (Kessler and Van Ullen, 2006). A significant improvement was expected in this follow-up study.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In 2006 when the authors examined the citation help available in databases, the quality of the help was disappointing. The previous study found that 94% of the citation examples examined had errors (Kessler and Van Ullen, 2006). A significant improvement was expected in this follow-up study.…”
Section: Discussionsupporting
confidence: 72%
“…In the first study, seven databases were examined: EBSCO Academic Search Premier, Gale In this present study, the overall error rate (including examples, pre-formatted citations and citations-on-demand) was 3.4 errors per citation versus an error rate of 4.4 errors per citation in the prior study (Kessler and Van Ullen, 2006). However, these results are not directly comparable as some of the databases examined varied between the two studies.…”
Section: Discussioncontrasting
confidence: 55%
“…A prior study examined citations created in EndNote as well as two citation generators, Easy Bib and NoodleBib, and found an error rate of 2.12 errors per citation (Kessler and Van Ullen, 2005). A review of citation help in databases revealed an error rate of 4.4 errors per citation (Kessler and Van Ullen, 2006). A later follow-up found an error rate of 3.4 errors per citation (Van Ullen and Kessler, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The 2005 study looked at sources taken from actual student bibliographies and included print and online journal articles, books, and web sites (Kessler and Van Ullen, 2005). The two studies on citation help in databases focused on journal articles (Kessler and Van Ullen, 2006;Van Ullen and Kessler, 2012). Citations for journal articles are appreciably more complex than citations for print books and there are more elements required.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study of these early attempts to help students cite found that the examples provided had errors 94 per cent of the time, and the examples averaged 4.4 errors each (Kessler and Mary, 2006). At the time, only one vendor was offering pre-formatted citations, and only one other was offering citations on demand.…”
Section: Citation Difficulties Facing Studentsmentioning
confidence: 99%